2021
DOI: 10.1155/2021/8352683
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Potentially Functional circRNA-miRNA-mRNA Network in Intervertebral Disc Degeneration by Bioinformatics Analysis

Abstract: Background. The competing endogenous RNA- (ceRNA-) mediated regulatory mechanisms are known to play a pivotal role in intervertebral disc degeneration (IDD). Our research intended to establish a ceRNA regulatory network related to IDD through bioinformatics analyses. Methods. The expression profiles of circRNA, miRNA, and mRNA were obtained from the public Gene Expression Omnibus (GEO) datasets. Then, we use sequence-based bioinformatics methods to select differentially expressed mRNAs (DEmRNAs), microRNAs (DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Harada et al showed that NRF2 could regulate intracellular iron metabolism and was associated with oxidative stress and ferroptosis in macrophages [ 96 ]. Existing evidence has demonstrated that circular RNA, a non-coding RNA, can bind to micro RNA to regulate the expression of its target genes [ 97 , 98 ]. Yu et al suggested that circ_0072464 in bone marrow mesenchymal stem cell (BMSC)-derived extracellular vesicles could increase NRF2 synthesis and alleviate ferroptosis in mouse NP cells by binding to miR-431 [ 14 ].…”
Section: Potential Mechanisms Of Ferroptosis In Ivddmentioning
confidence: 99%
“…Harada et al showed that NRF2 could regulate intracellular iron metabolism and was associated with oxidative stress and ferroptosis in macrophages [ 96 ]. Existing evidence has demonstrated that circular RNA, a non-coding RNA, can bind to micro RNA to regulate the expression of its target genes [ 97 , 98 ]. Yu et al suggested that circ_0072464 in bone marrow mesenchymal stem cell (BMSC)-derived extracellular vesicles could increase NRF2 synthesis and alleviate ferroptosis in mouse NP cells by binding to miR-431 [ 14 ].…”
Section: Potential Mechanisms Of Ferroptosis In Ivddmentioning
confidence: 99%
“…Due to their circular structure, circRNAs identified as biomarkers for diagnosis and prognosis are not affected by RNA exonucleases and become relatively stable (Li et al, 2015;Zhang et al, 2018). Many complex diseases, including non-tumors, are influenced by circRNAs (Xiong et al, 2018;Huo et al, 2021). At present, an increasing number of researchers are focusing on the association between circRNAs and disease occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…However, our understanding of the mechanism by which circRNA impacts IVDD is still limited. circRNAs were recently reported to influence pathogenic processes of IVDD including inflammation, ECM metabolism, NP cell proliferation, autophagy, and apoptosis by acting as ceRNAs [ 266 , 299 , 300 , 301 ]. Thus, these newly discovered ceRNA interaction sites could be important targets for IVDD treatment [ 167 , 291 ].…”
Section: Autophagy As a Potential Therapeutic Target For Ivddmentioning
confidence: 99%